Isolation of biosurfactant producing microorganisms and lipases from wastewaters from slaughterhouses and soils contaminated with hydrocarbons - Becerra, Lizzie (2016)
Surfactants are amphipathic molecules which reduce stress at the interface, thereby increasing water solubility and availability of organic compounds are produced by bacteria, fungi, and yeasts. For the isolation of biosurfactant producing bacteria and lipases, was plant in inducing means 10% of sewage effluent from slaughterhouses and soils contaminated with hydrocarbons Province taps Trujillo - Peru. Isolates were seed in agar cultures lecithin and rhodamine agar for determination of lipase producers. The selected microorganisms were plate on blood agar and agar Siegmund and Wagner (SW) for preliminary selection of biosurfactants bacteria. Later it determined to those microorganisms producing surfactants by Emulsification Index (EI) and measurement of surface tension. Positive cultures these tests were select and identified by API galleries and molecular identification by DNA sequencing. Crops further reduced surface tension were P. aeruginosa and B. amyloliquefaciens, reaching reduce surface tension to 27.2 ± 0.4 and 31.03 ± 0.4 mN / m respectively, while P. stutzeri and Pseudomonas sp. reduced surface tension to 48.3 and 52.6 ± 0.4 mN / m respectively. We conclude, therefore, that 49 producing crops lipases province Trujillo, of which it was determined that Pseudomonas stutzeri, Pseudomonas sp, Pseudomonas aeruginosa and Bacillus amyloliquefaciens are producers of biosurfactants and can be applied in the area of biotechnology was obtained environmental for the removal and biodegradation of contaminants.